The Influence of Compensation, Flexible Working Arrangement and Organizational Culture on Organizational Performance With Employee Engagement Mediation in Business Division of A Telco Company in Indonesia - Rosnawati Siregar; Nia Kusuma Wardhani (Dinasti International Journal of Management Science, 2023)
The study aims to analyze the factors that will affect organizational performance. Those factors include compensation, flexible working arrangement (FWA), organizational culture and employee engagement. This study will examine the effect of compensation, FWA and organizational culture on employee engagement. Moreover, it will analyze how employee engagement mediates the effect of compensation, FWA and organizational culture on organizational performance. The population in this study accounted for 115 permanent employees in the Business Division of a telecommunication company in Indonesia. The sample consisted of 90 employees using the Slovin formula calculation. The sampling technique used in this study is a simple random sampling technique. The sample was chosen randomly without regard to strata in the population. The research method used is quantitative explanatory with SEM-PLS. According to the analysis of the study, the result has proved that: compensation, FWA and organizational culture have positive and significant effects on employee engagement; compensation, organizational culture and employee engagement have positive and significant effects on organizational performance; FWA has no significant effect on organizational performance; Employee engagement mediates the effects of compensation, FWA and organizational culture on organizational performance.